Testing reciprocal relationships between marital attitudes, time spent together, and marital satisfaction among newlyweds: a cross-lagged path model - Luu, Sharon (Kansas State University, 2013)
The present study tests the reciprocal relationships between marital attitudes, time spent together, and marital satisfaction in a sample of newlyweds (N = 1220). Using cognitive dissonance theory and the investment model, this study tests two sets of theoretically derived unidirectional pathways to provide empirical evidence for longitudinal associations between these three constructs. Two separate models were tested, one for husbands, and one for wives. For both husbands and wives, results of the panel models indicated significant autoregressive paths among all three variables from T1 to T2, T2 to T3, and T1 to T3. Among husbands, significant cross-lagged paths emerged between T1 marital satisfaction and T2 marital attitudes, T1 marital satisfaction and T2 time spent together, T1 time spent together and T2 marital satisfaction, T2 time spent together and T3 marital satisfaction, and T2 time spent together and T3 marital attitudes. For wives, cross-lagged paths between T1 marital satisfaction and T2 time spent together, T1 time spent together and T2 marital satisfaction, and T2 time spent together and T3 marital satisfaction were found to be significant. Bootstrap test for indirect effects resulted in no significant mediating effects in the models. The results of these models are discussed and implications for future research and intervention are given.
Keywords: Reciprocal relationship; Marital attitudes; Time spent together; Marital satisfaction; Cross-lagged; Newlyweds; Social Research (0344)